Pengaruh Penggunaan Bahasa Indonesia dalam Peningkatan Komunikasi Remaja Antar Daerah pada Mahasiswa UBP Karawang - Feby Sulistio; Tridays Repelita; Agus Hariyadi; Ahmad Salim; Hanum Zalfa Muliana Wijaya (Journal on Education, 2024)
The use of Indonesian as the national language has a significant role in improving communication between regions in Indonesia. This article discusses how Indonesian facilitates ease of communication, strengthens unity, and provides fair access to education for youth in university environments. The method used in this research is a literature observation methodology to examine the impact of using Indonesian on improving communication among teenagers from various regions within UBP University. However, the challenge is that there is still a lack of good and correct Indonesian language management. Case studies show that increasingly intensive Indonesian language learning programs can improve the quality of communication and reduce misunderstandings. In conclusion, the use of Indonesian is an important tool in strengthening communication and unity between youth between regions, although improvements and improvements are needed